Contributions of K(ATP) and K(Ca) channels to cerebral arteriolar dilation to hypercapnia in neonatal brain - Nnorom, Chukwuma C. (Physiol Rep, 2014)
Mechanisms by which Pco(2) controls cerebral vascular tone remain uncertain. We hypothesize that potassium channel activation contributes to the neonatal cerebrovascular dilation in response to increases in Paco(2). To test this hypothesis, experiments were performed on newborn pigs with surgically implanted, closed cranial windows. Hypercapnia was induced by ventilation with elevated Pco(2) gas in the absence and presence of the K(ATP) channel inhibitor, glibenclamide and/or the K(Ca) channel inhibitor, paxillin. Dilations to pinacidil, a selective K(ATP) channel activator, without and with glibenclamide, were used to evaluate the efficacy of K(ATP) channel inhibition. Dilations to NS1619, a selective K(Ca) channel activator, without and with paxillin, were used to evaluate the efficacy of K(Ca) channel inhibition. Cerebrovascular responses to the K(ATP) and K(Ca) channel activators, pinacidil and NS1619, respectively, cAMP‐dependent dilator, isoproterenol, and cGMP‐dependent dilator, sodium nitroprusside (SNP), were used to evaluate the selectivity of glibenclamide and paxillin. Glibenclamide blocked dilation to pinacidil, but did not inhibit dilations to NS1619, isoproterenol, or SNP. Glibenclamide prior to hypercapnia decreased mean pial arteriole dilation ~60%. Glibenclamide treatment during hypercapnia constricted arterioles ~35%. The level of hypercapnia, Paco(2) between 50 and 75 mmHg, did not appear to be involved in efficacy of glibenclamide in blocking dilation to Paco(2). Similarly to glibenclamide and K(ATP) channel inhibition, paxillin blocked dilation to the K(Ca) channel agonist, NS1619, and attenuated, but did not block, arteriolar dilation to hypercapnia. Treatment with both glibenclamide and paxillin abolished dilation to hypercapnia. Therefore, either glibenclamide or paxillin that block dilation to their channel agonists, pinacidil or NS1619, respectively, only partially inhibit dilation to hypercapnia. Block of both K(ATP) and K(Ca) channels completely prevent dilation hypercapnia. These data suggest hypercapnia activates both K(ATP) and K(Ca) channels leading to cerebral arteriolar dilation in newborn pigs.